2018
DOI: 10.1186/s41747-018-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema quantification using chest CT: influence of radiation dose reduction and reconstruction technique

Abstract: BackgroundComputed tomography (CT) emphysema quantification is affected by both radiation dose (i.e. image noise) and reconstruction technique. At reduced dose, filtered back projection (FBP) results in an overestimation of the amount of emphysema due to higher noise levels, while the use of iterative reconstruction (IR) can result in an underestimation due to reduced noise. The objective of this study was to determine the influence of dose reduction and hybrid IR (HIR) or model-based IR (MIR) on CT emphysema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
2
28
0
1
Order By: Relevance
“…Previous studies already showed that dose reduction, post processing, and IR can affect the quantitative measurement of emphysema [15, 16]. To the best of our knowledge, this is the first study that showed that the hybrid IR levels of iDose 4 have a significant influence on the amount of emphysema that is quantified by means of post processing in a low dose scan.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies already showed that dose reduction, post processing, and IR can affect the quantitative measurement of emphysema [15, 16]. To the best of our knowledge, this is the first study that showed that the hybrid IR levels of iDose 4 have a significant influence on the amount of emphysema that is quantified by means of post processing in a low dose scan.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, the threshold of 0.20 to calculate percentage of low-signal-intensity volume cannot be thought of as generalizable. Nonetheless, recent data have demonstrated that adaptation of thresholds may also be necessary with CT techniques of dose reduction (35). Sixth, the spatial resolution of MRI is still lower than that of CT and we did not perform a lobar evaluation.…”
Section: Supportive Evaluations Of Mri Validitymentioning
confidence: 88%
“…Apart from that, the thresholding approach used to obtain the emphysema index is very sensitive to noise in the reconstructed images (and thus also to the used reconstruction algorithm, slice thickness, and dose), since affected and healthy tissue exhibit similar density values. 38,39 For this reason, the differentiation of early disease stages using the CT emphysema index is limited. 36 This is also apparent from our findings for the tendency across the Fleischner grades where all groups until moderate emphysema yield mean index values below the critical value of 6%.…”
Section: Discussionmentioning
confidence: 99%